Post-9/11 Terrorism Threats, News Coverage, and Public Perceptions in the United States - Brigitte L. Nacos; Yaeli Bloch-Elkon; Robert Y. Shapiro (International Journal of Conflict and Violence, 2007)
Terrorists, policy-makers, and terrorism scholars have long assumed that the mere threat of terrorist strikes affects societies that have experienced actual acts of terrorism. For this reason, most definitions of terrorism include the threat of violent political acts against civilians. But so far research has neither validated this conventional wisdom nor demonstrated how actual and mass-mediated threat messages by terrorists and terror alerts and threat assessments by government officials affect the public in targeted states. This paper fills the gap providing evidence that who conveys such messages matters and that mass-mediated threat messages by al Qaeda leaders and announced alerts and threat assessments by U.S. administration officials had a significant impact on the American public’s threat perceptions in the post-9/11 years.